2017
DOI: 10.1002/2016ja023401
|View full text |Cite
|
Sign up to set email alerts
|

A direct examination of the dynamics of dipolarization fronts using MMS

Abstract: Energy conversion on the dipolarization fronts (DFs) has attracted much research attention through the suggestion that intense current densities associated with DFs can modify the more global magnetotail current system. The current structures associated with a DF are at the scale of one to a few ion gyroradii, and their duration is comparable to a spacecraft's spin period. Hence, it is crucial to understand the physical mechanisms of DFs with measurements at a timescale shorter than a spin period. We present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 72 publications
7
45
1
Order By: Relevance
“…It reveals in particular the formation of the EDR as identified by the enhancement of j ⋅ E ′ near the X line . Negative j ⋅ E ′ dips were also reported in Cluster and MMS observations of DFs (Khotyaintsev et al, 2017;Yao et al, 2017), as well as MMS observations of the EDR vicinity at the magnetopause . They were identified earlier (Sitnov et al, 2014) as signatures of the long-wavelength (∼ 2 √ 0i 0e ) modification (Daughton, 2003) of the lower-hybrid drift instability (LHDI) of thin CSs with zero B z component (Huba et al, 1977), which is also similar in case of nonzero B z to the kinetic ballooning/interchange instability (Pritchett & Coroniti, 2010).…”
Section: Simulation Setup and Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…It reveals in particular the formation of the EDR as identified by the enhancement of j ⋅ E ′ near the X line . Negative j ⋅ E ′ dips were also reported in Cluster and MMS observations of DFs (Khotyaintsev et al, 2017;Yao et al, 2017), as well as MMS observations of the EDR vicinity at the magnetopause . They were identified earlier (Sitnov et al, 2014) as signatures of the long-wavelength (∼ 2 √ 0i 0e ) modification (Daughton, 2003) of the lower-hybrid drift instability (LHDI) of thin CSs with zero B z component (Huba et al, 1977), which is also similar in case of nonzero B z to the kinetic ballooning/interchange instability (Pritchett & Coroniti, 2010).…”
Section: Simulation Setup and Resultssupporting
confidence: 55%
“…In particular, it cannot be limited by the standard resistive magnetohydrodynamic (MHD) parameters (Birn & Hesse, 2005;Zenitani et al, 2011), i.e., the energy conversion rates in the frame moving with ions or electrons j ⋅ E ′ e,i , where j = j i + j e , E ′ e,i = E+v e,i ×B∕c, j e,i are the electron/ion currents in the laboratory frame of reference and v e and v i are the electron and ion bulk flow velocities. In addition, recent MMS observations and analysis Genestreti et al, 2017;Yao et al, 2017) revealed regions of large negative values of the j ⋅ E ′ parameter, comparable in magnitude to its positive peaks in the electron diffusion region (EDR). Thus, they are reduced to a single MHD parameter j ⋅ E ′ ≈ j ⋅ E ′ e,i , also known as the Joule heating rate, which cannot be used to distinguish between electron and ion dissipation processes (see, e.g., similar profiles of j ⋅ E ′ e and j ⋅ E ′ i in Figure 6 in Yao et al, 2017).…”
Section: 1029/2018gl077874mentioning
confidence: 92%
“…Using three‐dimensional PIC simulation, Pritchett et al () showed that J · E ′ can be either positive or negative at DF. In particular, Yao et al () found a large negative J · E ′ at a DF by MMS observations.…”
Section: Introductionmentioning
confidence: 96%
“…It should be noted that J · (E+v i × B) = J · (E+v e × B) when assuming charge neutrality (n i = n e ). Thus, it cannot be used to distinguish the dissipation between electrons and ions (Sitnov et al, ; Yao et al, ). In MHD theory, it describes the change of local entropy (Birn & Hesse, ).…”
Section: Introductionmentioning
confidence: 99%
“…The current density peak of the bifurcated current sheet does not coincide with the neutral line, and it is generally suggested that it is related to the Hall effect currents generated in separatrix region (e.g., Runov et al 2003). The complicated current system may be also related to the reconnection front current structures (Yao et al 2013), in which parallel current density is carried by electrons (Yao et al 2016), and perpendicular currents are mainly carried by ions (Yao et al 2017). These studies imply that the current system in the separatrix region is an essential element in the reconnection process.…”
Section: Introductionmentioning
confidence: 99%